Carbon bio-fixation, effect of physicochemical factors and carbon supply strategies by Nannochloropsis sp. using flue gas and fertilizer. (June 2019) - Banerjee, Avik; Guria, Chandan; Maiti, Subodh Kumar; Banerjee, Chiranjib; Shukla, Pratyoosh
Abstract: As atmospheric CO2 is rising alarmingly, focused research on microalgal based bio-mitigation of CO2 has become relevant. With the aim of single-objective maximization, response surface methodology (RSM) study was employed through central composite design (CCD) for the phototropic cultivation of Nannochloropsis sp. using Flue gas and synthetic fertilizer (NPK-10:26:26). Influence of crucial external factors such as light, salinity, carbon content and nutrients were investigated along with their interactions on three objectives such as Biomass, Lipid, and carbon bio-fixation rate. Using fertilizer assisted RSM optimized media, an enhancement of 43, 31, and 79% was observed in three responses over standard f/2 medium. Variation in carbon content (32%) and C/N ratio (100%) was observed, that validated diversion of metabolism under stress. The multi-objective optimization was carried out by genetic algorithm. A carbon supply strategy was employed that enhances biomass growth. Carbon sequestration was calculated first time precisely. Light intensity was concluded as a dominant external inducer to carbon-sequestration and lipid accumulation. Carbon sequestration rate was revealed to enhance in conditions that favor both good growths and induce stress. Single and multi-objective optimization data in this study can help in commercial decision making required in large scale-cultivations for biotechnological gains. Graphical abstract: Image 1 Highlights: Lipid, biomass and carbon fixation rate of Nannochloropsis sp. optimized by RSM: the values obtained are 1.23 g l −1, 51% and 0.221 g l −1 d −1 . Role of external factors on carbon sequestration rate quantified. Light reported to be a dominant inducer of lipid. Stress is optimized for CO2 fixation. Variation of Nannochloropsis. sp. cellular composition: av. carbon content (42.25–55.6%) and C/N ratio (7.3–14.62) under stress demonstrated. Optimization of multi-objective like biomass-lipid-carbon fixation was carried out. Need based (Lipid or biomass) commercial cultivation can be done based that.